ENDOPHTHALMITIS AFTER PARS PLANA VITRECTOMY: Efficacy of Intraoperative Subconjunctival Antibiotics. Issue 9 (September 2018) - Weiss, Stephanie J.; Adam, Murtaza K.; Gao, Xinxiao; Obeid, Anthony; Sivalingam, Arunan; Fineman, Mitchell S.; Maguire, Joseph I.; Garg, Sunir J.; Haller, Julia; Fischer, David H.; Hsu, Jason
Abstract : Purpose: To examine rates of acute infectious endophthalmitis after pars plana vitrectomy (PPV) in eyes that received intraoperative subconjunctival antibiotics versus eyes that did not. Methods: A retrospective, nonrandomized, comparative case series of 18, 886 consecutive cases of transconjunctival 23-, 25-, and 27-gauge PPV over a 5-year period was performed. The impact of prophylactic intraoperative subconjunctival antibiotics on the development of acute infectious postoperative endophthalmitis was examined. Results: Of 18, 886 cases of PPV, 14, 068 (74.5%) received intraoperative subconjunctival antibiotics, whereas 4, 818 (25.5%) did not. Sixteen cases (0.085%, 1/1, 176) of post-PPV endophthalmitis were identified. The incidence of endophthalmitis in eyes that received subconjunctival antibiotics was 0.078% (11/14, 068 cases, 1/1, 282), whereas the incidence in those that did not receive subconjunctival antibiotics was 0.10% (5/4, 818 cases, 1/1, 000). No statistically significant difference was identified in the incidence of endophthalmitis between those that received subconjunctival antibiotics and those that did not ( P = 0.598). Microbial culture was performed in 11 cases with 6 culture-positive cases (5/8 cases that received subconjunctival antibiotics and 1/3 cases that did not). Conclusion: Prophylactic subconjunctival antibiotics were not associated with a significantly reduced rate of post-PPV endophthalmitis. With consideration of emerging multidrug-resistant bacteria, routine prophylactic subconjunctival antibiotics may not be justified. Abstract : Endophthalmitis is a rare complication of pars plana vitrectomy, occurring in 0.085% of cases. Routine prophylactic subconjunctival antibiotic injections were not associated with a significantly reduced rate of postoperative endophthalmitis and may not be justified.